Toward semantic similarity measure between concepts in an ontology - Suwan Tongphu; Boontawee Suntisrivaraporn; Pakinee Aimmanee (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A similarity measure is one classical problem in Description Logic which aims at identifying the similarity between concepts in an ontology. Finding a hierarchy distance among concepts in an ontology is one popular technique. However, one major drawback of such a technique is that it usually ignores a concept definition analysis. This work introduces a new method for similarity measure. The proposed system semantically analyzes structures of two concept descriptions and then computes the similarity score based on the number of shared features. The efficiency of the proposed algorithm is measured by means of the satisfaction of desirable properties and intensive experiments on the Snomed ct ontology.